2000
DOI: 10.1046/j.1365-2672.2000.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phenolic compounds on the physiology of OEnococcus oeni from wine

Abstract: This study shows that the growth of Oenococcus oeni CECT 4100 in a synthetic medium is affected by phenolic compounds in different ways, depending on their type and concentration. Generally they have no effects at low concentrations, but hydroxycinnamic acids are inhibitory at high concentrations. Malolactic fermentation was stimulated in the presence of catechin and quercetin, but increasingly delayed with increasing amounts of p-coumaric acid. Gallic acid appeared to delay or inhibit the formation of acetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 15 publications
6
110
0
Order By: Relevance
“…Phenolic compounds, in turn, can affect the growth and metabolism of LAB (Alberto et al, 2007) and also the occurrence and progression of MLF (Vivas et al, 1997a). Phenolic acids inhibit the growth of LAB (Reguant et al, 2000;Knoll et al, 2008), while flavan-3-ols and flavonols can stimulate the growth of specifically Oenococcus oeni (Vivas et al, 1997a;Rozès et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds, in turn, can affect the growth and metabolism of LAB (Alberto et al, 2007) and also the occurrence and progression of MLF (Vivas et al, 1997a). Phenolic acids inhibit the growth of LAB (Reguant et al, 2000;Knoll et al, 2008), while flavan-3-ols and flavonols can stimulate the growth of specifically Oenococcus oeni (Vivas et al, 1997a;Rozès et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds may affect growth and metabolism of bacteria. They could have an activating or inhibiting effect on microbial growth according to their constitution and concentration (Reguant et al, 2000). Tannins are well known to possess general antimicrobial properties reported by Scalbert, (1991).…”
mentioning
confidence: 99%
“…Phenolic compounds may affect growth and metabolism of bacteria. They could have an activating or inhibiting effect on microbial growth according to their constitution and concentration [22] . Zapata and McMillan reported that the phenolic compounds present in seagrasses could also enhance the antimicrobial activity [23] .…”
Section: Discussionmentioning
confidence: 99%